1995
DOI: 10.1007/bf02990058
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up study of thyroid function in polytransfused thalassemic patients

Abstract: The aim of our investigation was to evaluate thyroid function by a follow-up study in 45 polytransfused thalassemic patients, since endocrine abnormalities are frequent consequences of iron overload in thalassemia major. Significant changes of thyroid function have been revealed in the time elapsing the observation, despite unchanged haematological parameters; at the end of the present study five patients were affected by overt hypothyroidism and 15 patients by subclinical hypothyroidism. Ultrasound thyroid vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In the past ten years new therapeutic trends (hypertransfusion regimen and iron chelation therapy) have prolonged life expectancy of transfusion-dependent thalassemic patients (Zurlo et al, 1989), hence raising clinical relevance of several endocrinopathies (Borgna et al, 1990;De Sanctis et al, 1992;Maggiolini et al, 1995). In recent studies it has been indicated that nowadays most of these patients enter puberty spontaneously (Olivieri et al, 1990), so that pathophysiological aspects which concern reproductive function are also of particular interest.…”
Section: Introductionmentioning
confidence: 99%
“…In the past ten years new therapeutic trends (hypertransfusion regimen and iron chelation therapy) have prolonged life expectancy of transfusion-dependent thalassemic patients (Zurlo et al, 1989), hence raising clinical relevance of several endocrinopathies (Borgna et al, 1990;De Sanctis et al, 1992;Maggiolini et al, 1995). In recent studies it has been indicated that nowadays most of these patients enter puberty spontaneously (Olivieri et al, 1990), so that pathophysiological aspects which concern reproductive function are also of particular interest.…”
Section: Introductionmentioning
confidence: 99%